2013
DOI: 10.1016/j.injury.2012.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Procedural justice and quality of life in compensation processes

Abstract: The finding that the interaction with insurance companies was considered less fair than the interaction with lawyers may imply that insurers could improve their interaction with claimants, e.g. by communicating more directly. The result that claimants with mild injuries and with trunk/back injuries considered the compensation process to be less fair than those with respectively severe injuries and injuries to other body parts suggests that especially the former two require an attentive treatment. Finally, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Secondly, that the insurance claim itself may lead to a worsened outcome. It has been shown that an ongoing compensation process affects the claimants' quality of life negatively, both physically and mentally [13,22] and that a prolonged time to claim closure is a negative prognostic parameter [13,23]. Indirectly, this could be correlated with being an experience of non-recovery after the index trauma [24] and support the "compensation theory" [14].…”
Section: Discussionmentioning
confidence: 88%
“…Secondly, that the insurance claim itself may lead to a worsened outcome. It has been shown that an ongoing compensation process affects the claimants' quality of life negatively, both physically and mentally [13,22] and that a prolonged time to claim closure is a negative prognostic parameter [13,23]. Indirectly, this could be correlated with being an experience of non-recovery after the index trauma [24] and support the "compensation theory" [14].…”
Section: Discussionmentioning
confidence: 88%
“…Low website usage could also have been caused by the fact that the participants in the sample were somewhat older than average (48 versus 39): generally, older people are not as familiar with the internet as younger people. Low website usage did not seem to be caused by any dislike of the appeal, content, or structure of the website, because the questions evaluating these aspects were answered quite positively, except that they indicated not needing an e-coach (7.3 on a scale from 1 to 10) (which is remarkable because their health was significantly poorer than that of the average Dutch population (6.3 versus 8.3 [28]).…”
Section: Discussionmentioning
confidence: 99%
“…Few qualitative studies have identified factors that largely depend on a person's environment and health‐care and compensation systems . Others reported factors such as lack of family support, legal involvement and the compensation claim . However, it is still unclear how these factors impact the recovery outcome; how they interact; and which from an injured person's perspective are the most important to measure to identify people at high risk for poor recovery.…”
Section: Introductionmentioning
confidence: 99%